Effect of co-activation of tongue protrudor and retractor muscles on tongue movements and pharyngeal airflow mechanics in the rat - Fuller, D D (Blackwell Science Inc, 1999)
1. The purpose of these experiments was to examine the mechanisms by which either co-activation or independent activation of tongue protrudor and retractor muscles influence upper airway flow mechanics. We studied the influence of selective hypoglossal (XIIth) nerve stimulation on tongue movements and flow mechanics in anaesthetized rats that were prepared with an isolated upper airway. In this preparation, both nasal and oral flow pathways are available. 2. Inspiratory flow limitation was achieved by rapidly lowering hypopharyngeal pressure (P(hp)) with a vacuum pump, and the maximal rate of flow (V(I,max)) and the nasopharyngeal pressure associated with flow limitation (P(crit)) were measured. These experimental trials were repeated while nerve branches innervating tongue protrudor (genioglossus; medial XIIth nerve branch) and retractor (hyoglossus and styloglossus; lateral XIIth nerve branch) muscles were stimulated either simultaneously or independently at frequencies ranging from 20-100 Hz. Co-activating the protrudor and retractor muscles produced tongue retraction, whereas independently activating the genioglossus resulted in tongue protrusion. 3. Co-activation of tongue protrudor and retractor muscles increased V(I,max) (peak increase 44 %, P < 0.05), made P(crit) more negative (peak decrease of 44 %, P < 0.05), and did not change upstream nasopharyngeal resistance (R(n)). Independent protrudor muscle stimulation increased V(I,max) (peak increase 61 %, P < 0.05), did not change P(crit), and decreased R(n) (peak decrease of 41 %, P < 0.05). Independent retractor muscle stimulation did not significantly alter flow mechanics. Changes in P(crit) and V(I,max) at all stimulation frequencies were significantly correlated during co-activation of protrudor and retractor muscles (r(2)= 0.63, P < 0.05), but not during independent protrudor muscle stimulation (r(2)= 0.09). 4. These findings indicate that either co-activation of protrudor and retractor muscles or independent activation of protrudor muscles can improve upper airway flow mechanics, although the underlying mechanisms are different. We suggest that co-activation decreases pharyngeal collapsibility but does not dilate the pharyngeal airway. In contrast, unopposed tongue protrusion dilates the oropharynx, but has a minimal effect on pharyngeal airway collapsibility.